2016
DOI: 10.15407/ubj88.02.056
|View full text |Cite
|
Sign up to set email alerts
|

Level of overall hemostasis potential in donor and patient plasma in pathology

Abstract: Coagulation potential (CP), overall hemostasis potential (OHP) and fibrinolysis potential (FP) in plasma of donors and patients with myocardial infarction (MI), stroke (St) and hip joint diseases (HJD) have been investigated using M. Blomback’s global hemostasis assay. Plasma samples of the patients were analyzed with APTT reagent in the presence or absence of t-PA. It was found that the ratio of values of СP, OHP and FP in plasma of patients to those of donors plasma were 78, 60 and 123% at MI; 157, 155 and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…In the previous article, we found that between the parameters of the hemostasis potential determined by the method of M. Blomback [4], which show the ability of blood plasma hemostasis system in vitro to form and dissolve the fibrin clot, and molecular markers of the hemostasis system in plasma of blood in vivo, which characterize the state of the hemostasis system at the moment of the blood sample withdrawing in patients with myocardial infarction, stroke or hip joint disease, no strong correlation was observed [4].…”
Section: The Values Of the Coagulation Overall And Fibrinolysis Potementioning
confidence: 92%
See 2 more Smart Citations
“…In the previous article, we found that between the parameters of the hemostasis potential determined by the method of M. Blomback [4], which show the ability of blood plasma hemostasis system in vitro to form and dissolve the fibrin clot, and molecular markers of the hemostasis system in plasma of blood in vivo, which characterize the state of the hemostasis system at the moment of the blood sample withdrawing in patients with myocardial infarction, stroke or hip joint disease, no strong correlation was observed [4].…”
Section: The Values Of the Coagulation Overall And Fibrinolysis Potementioning
confidence: 92%
“…The overall hemostasis potential (OHP) is characterized by the size of area under curve of the clot turbidity from the moment the plasma coagulation is initiated to the moment when turbidity completely disappeared in the presen ce of t-PA. Coagulation potential (CP) is the area under curve of the clot formation in the absence of t-PA from the moment of plasma coagulation initiation to the moment of complete dissolution of the clot in the presence of t-PA. Fibrinolysis potential (FP) is the difference between the magnitudes of CP and OHP. All values of potentials are expressed in units of optical density multiplied by time in seconds (o. u.•s) [4,6].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall hemostasis potential (OHP) was characterized by the area under the turbidity curve of the clot from the moment of initiation of plasma coagulation to the moment of complete destruction of the clot in the presence of t-PA. Coagulation potential (CP) -the area under the curve of clot formation from the moment of initiation of plasma coagulation to the moment of complete dissolution of the clot in the absence of t-PA. Fibrinolytic potential (FP)isthedifferencebetweenthevaluesofCPand OHP. All values were expressed in units of optical density multiplied by time in seconds (o.u.•s) [12,13].…”
Section: Methodsmentioning
confidence: 99%
“…The individual stages of the process of clot formation and hydrolysis were characterized by thefollowingparameters:τ(s)-lagperiod,which shows the rate of activation of the internal path of the coagu lationcascade,thrombinformation,fibrinogenactivationintofibrinandprotofibrilformation; α(V 1 ) o.u./s -tg of the angle of inclination of the maximum rate of growth of the clot turbidity, which showstherateoflateralassociationofprotofibrils andtheformationoffibrils;H(o.u. )-themagnitude ofthefinalturbidityoftheclot,whichisdetermined bythethicknessofthefibrilsoftheclot;L(s)isthe half-life of the clot, which depends on the concentration of plasminogen, t-PA and the structure of theclot;β(-V 2 )-о.u./s-tgoftheangleofinclination of the maximum rate of falling of turbidity of a clot which depends on concentration of plasmin and plasmininhibitors(α2-antiplasmin,PAI-1)inblood plasma [13].…”
Section: Methodsmentioning
confidence: 99%